APPLICATION OF AUGMENTED LAGRANGE MULTIPLIER METHOD AS A PARAMETER PENALTY ON THE OPTIMIZATION CROSS-SECTIONAL AREA OF A TRUSS TO MINIMIZE WEIGHT USING GENETIC ALGORITHM - ( NIM : 20113059), ADRIYANSYAH
The optimization is a process to achieve optimum results. The optimization in structural engineering design process to obtain a strong structure, light wight structure and safe structure(satisfy the constraints given). To obtain optimum results in the optimization process is very dependent algorithm used. This thesis discusses the cross-sectional area optimization truss with stress constraint, risk, and displacement. Constraints optimization converted into a problem without constraints by summing the constraint is violated to the objective function in the form of penalty function. Parameter penalty searched using Augmented Lagrange Multiplier (ALM) and process optimization solved by genetic algorithm.